A24 Genetic Counselling. (17th September 2014) - MacLeod, R; Lahiri, N
Abstract : "Genetic counselling is the process of helping people understand and adapt to the medical, psychological and familial implications of genetic contributions to disease" (NSGC, 2006). In the 20 years since the discovery of the HD gene, guidelines for predictive testing in Huntington's disease have become a model for genetic counselling across a wide range of inherited conditions. Experience has shown that while many individuals wish to know their genetic status, far fewer actually undergo testing. The predictive testing guidance has been updated in recent years to reflect changes in clinical practice over time and are designed to act as a framework of recommended procedures, rather than regulations, to reflect the uniqueness of each individual wishing to discuss their risk of HD. In this interactive case-based workshop we will consider how genetic counselling for HD can be tailored to meet the needs of the individual and their family. We will look at some of the more challenging genetic counselling situations, such as non-disclosure of genetic information to children at risk of HD, and dealing with the problems of denial of symptom onset where this is causing problems at work or in the home. Research evidence in relation to the provision of genetic counselling services will be highlighted and suggestions made for areas where practice may be enhanced for the benefit of family members.